Microservices vs. Monolithic Architectures: Strategic Trade-Offs in the AI Era - Rajesh Vasa, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive analysis of the strategic trade-offs between microservices and monolithic architectures in the context of artificial intelligence integration. Through examination of empirical data from enterprise deployments across multiple sectors, the article demonstrates that AI-enhanced microservices achieve significant improvements in system performance, scalability, and operational efficiency. The article reveals that organizations implementing AI-enabled microservices experience substantial reductions in deployment cycles, marked improvements in system reliability, and considerable decreases in operational overhead. The article analysis encompasses intelligent monitoring systems achieving high accuracy in anomaly detection, dynamic resource optimization reducing operational costs, and self-healing mechanisms decreasing mean time to recovery. The article also addresses implementation challenges, including operational complexity and data management considerations, while providing evidence-based recommendations for successful adoption. The findings indicate that the integration of AI capabilities fundamentally transforms traditional architectural trade-offs, offering organizations unprecedented opportunities for innovation and efficiency improvements in their digital transformation journey.
Keywords: AI-Enhanced Microservices Architecture; Distributed System Resilience; Dynamic Resource Optimization; Edge Computing Integration; Intelligent System Monitoring